How do we know when the change is optimal? - Latu, Lazar; Latu, Roxana (Studies and Scientific Researches. Economics Edition, 2010)
The analysis of the external environment must not be limited to the identification of the external factors, but must also take into account their importance. The real management capacity consists of finding out their signification, of identifying exactly those factors which may have a special influence upon the organization. As a consequence of the fact that the external environment is dynamic, it is important to understand correctly the direction of the moment and the location of the change.